Transforming ordinary to extraordinary - Jorquera, Daniela; Brancoli , Bernardita (Base Diseño e Innovación, 2015)
Cupron is a company in Israel that permanently incorporates microscopic particles of copper to different substrates. They have achieved transforming common use products such as socks and pillows, into solutions to the health and well-being of the people.